(3GdaJhM ddhVhMs - (3Ydj (B((3CZG(B) (3Hf jhfS (B((3CZG(B) (3Hf YHO GdLdjd GdLdjdjs; (3GdLGQHQOj , CMeO Hf GdMSf Hf jhSa, aNQ GdOjf,J (B746 (3g` s
(3ChdgG (B:s
(3hHYO, ajbhd Ydj Efj deG bQCJ GdTQM GdeZfj cKjQ GdHQcI hGdeYGfj JCdja SjOj s
(3BNQgG (B:s
(3GdNGeS Jfhjf GdJQfe hGdSGOS Jfhjf dMb bGajI ebjOI ZjQ eWdbI hgj ddJQfe ceG aj bhd QDHI Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs